MAKTABGACHA YOSHDAGI BOLALARNING IQTISODIY BILIMLARINI RIVOJLANTIRISHDA O‘YINNING ROLI - Allaberganova, N.P. (SCIENCE and SOCIETY, 2023)
This article considers the specific characteristics and types of game activities in a preschool educational organization for the development of economic knowledge of preschool children. Information is given on determining the most effective game activities that help to develop economic knowledge of preschool children.